A significação de Nossa Senhora do Perpétuo Socorro: análise semiótica do Ícone e das práticas devocionais - Azevedo, Renan Ramires de (2024)
This study aimed to identify how the process of signification occurs concerning the icon and devotional practices of Our Lady of Perpetual Help. For this, we used the theoretical and methodological principles of Discourse Semiotics (Greimas, 1970), a French theory that focuses on the signification of texts through the analysis of their respective structures in the relation between content and expression (Hjelmslev, 2013 [1961]), which thus produces meaning. The corpus of this work, as previously mentioned, comprises the enunciations related to the figure of Our Lady of Perpetual Help, with a specific focus, for analytical demonstration, on the practices occurring at the Santuário Estadual de Nossa Senhora do Perpétuo Socorro (State Shrine of Our Lady of Perpetual Help), placed in Campo Grande, Mato Grosso do Sul, Brazil – as it has been the shrine that most extensively reproduces practices of this popular devotion in the country. More precisely, the corpus is organized into: a) the Novena of Our Lady of Perpetual Help – through the rite recorded in the Novenário/Pocketbook, the practice itself, and its online maintenance during the Covid-19 pandemic, through the recording of the rite on YouTube; b) the Icon of Our Lady of Perpetual Help and its placement in the sacred space; and c) excerpts of enunciations of Perpetual Help as the patroness of a place, in this case, selected excerpts include the litany and the consecration of the patroness of Mato Grosso do Sul, recited during the mass on the patroness's day at the same locus in question. For the analysis, the methodology of the generative process of meaning was employed, using the concepts of the fundamental level, the narrative level, and the discursive level in content analysis, as well as chromatic, eidetic, and topological categories in the pictorial expression analysis of the icon. Furthermore, this research presents tensive considerations regarding the tonicity of the ritual discourse genres in the Novena and the religious enunciators (God, Our Lady, and Saints in general) in the current Catholic rite, which, when related, exhibit a certain hierarchy. Thus, this research is situated within the tradition of semiotic studies about religion/religiosity, and based on the results obtained, we were able to understand, for instance, the textual organization of the enunciations of Our Lady of Perpetual Help, their themes and figures and how they relate, their enunciative functioning, among other contributing points. Through the dissemination of this research, we hope to introduce new semiotic objects in the religious discursive domain and provide new boundaries and meanings in the conception of the sacred in its various forms of manifestation.